(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: CNS tumors comprise 2% to 5% of all tumors. There was no epidemiological and statistical data regarding various features of brain tumors in this country. 80% involve the brain and 20% involve the spinal cord. Brain tumors cause approximately 2% of all cancer deaths. Objectives: to evaluate the clinical and pathological characteristics of brain tumors. Methods: This prospective study was done at Oncology department and Neurosurgery department of Bangabandhu Shiekh Mujib Medical University from July 2006 to June 2007. Total 50 patient age 2-60 years attending the oncology department with the diagnosis of primary brain tumor were included in this study. Clinical symptoms and sign in relation to brain tumor were recorded. X ray skull and CT scan reports of all cases were evaluated. To find out the histopathological pattern of the brain tumors all histopathological reports were also evaluated. Results: Most common symptoms of brain tumor were headache (76%), mental change (64%), vomiting (52%), visual defect (46%), difficulty in movement (42%) and convulsion (36%). Astrocytoma was found in 40% patients and 30% brain tumor was associated with hydrocephalus Conclusion: This study represent the brain tumor and gives some idea about the clinicopathological aspects of the disease in our country. It will help to do further studies to evaluate the clinical, epidemiological and pathological characteristics of brain tumor DOI: 10.3329/bsmmuj.v3i2.7054 BSMMU J 2010; 3(2): 68-71